Turismo accesible como alternativa para diversificar la oferta turística en la provincia de Cotopaxi. - Paneluisa Daquilema, Alison Mishel (2023)
Cotopaxi is one of the provinces with a great diversity of tourism offerings, however, it does not have adequate information regarding facilities and access for people with disabilities, this project was developed in order to have an overview of the situation of accessible tourism and how it would help of diversification of tourism in the province, determining existence of accessible tourism services. The research is part of a macro project on accessibility in the province, for this reason this project was developed only in Latacunga canton and focused specifically on lodging establishments. On the other hand, the research design is based on an exploratory and descriptive methodology, thus the first objective began with a literature review, synthesizing various definitions, theories and concepts that break down the topic, thus obtaining the basis study as support for theoretical framework, then statistical data were collected focused on the knowledge that the providers of this service have about mentioned topic, the second objective focused on verifying compliance with Ecuadorian Technical Standard (NTE)(2018), by 19 hotels that are active, and their level of accessibility through the use of a check list, where it was possible to verify that only 2 hotels DO comply with 78% of accessibility, while the remaining 17 DO NOT and therefore the hotel offer of the canton is NOT accessible, As a final objective, a scientific article was prepared for the RENPYS magazine based on study of the hotels, providing brief information about data obtained from the entire investigation, thus providing a contribution aimed at changing Latacunga as an accessible tourist destination, as well as contributing to promotion of the inclusion people with disabilities and other vulnerable groups.